Endothelial Reprogramming Stimulated by Oncostatin M Promotes Inflammation and Tumorigenesis in VHL -Deficient Kidney Tissue - Nguyen-Tran, Hieu-Huy; Nguyen, Thi-Ngoc; Chen, Chen-Yun; Hsu, Tien (Cancer research (Chicago, Ill.), 2021)
Clear-cell renal cell carcinoma (ccRCC) is the most prevalent subtype of renal cell carcinoma (RCC), and its progression has been linked to chronic inflammation. About 70% of the ccRCC cases are associated with inactivation of the von Hippel-Lindau ( ) tumor-suppressor gene. However, it is still not clear how mutations in , encoding the substrate-recognition subunit of an E3 ubiquitin ligase that targets the alpha subunit of hypoxia-inducible factor-α (HIFα), can coordinate tissue inflammation and tumorigenesis. We previously generated mice with conditional knockout in kidney tubules, which resulted in severe inflammation and fibrosis in addition to hyperplasia and the appearance of transformed clear cells. Interestingly, the endothelial cells (EC), although not subject to genetic manipulation, nonetheless showed profound changes in gene expression that suggest a role in promoting inflammation and tumorigenesis. Oncostatin M (OSM) mediated the interaction between -deficient renal tubule cells and the ECs, and the activated ECs in turn induced macrophage recruitment and polarization. The OSM-dependent microenvironment also promoted metastasis of exogenous tumors. Thus, OSM signaling initiates reconstitution of an inflammatory and tumorigenic microenvironment by -deficient renal tubule cells, which plays a critical role in ccRCC initiation and progression. SIGNIFICANCE: A novel mechanism of cross-talk between ECs and -deficient kidney tubules that stimulates inflammation and tumorigenesis is discovered, suggesting OSM could be a potential target for ccRCC intervention.